STOCK PRICE VOLATILITY DURING COVID-19: EVIDENCE FROM HOSPITALITY FIRMS IN INDONESIA - Wahyudi, Setyo Tri; Nabella, Rihana Sofie; Sari, Kartika; Musa, Ibrahim (EP FEB UNS, 2022)
This study aims to measure the volatility of stock prices of hospitality firms in Indonesia during the Covid-19 pandemic. Using the stock prices data on hospitality firms and the Autoregressive Integrated Moving Average (ARIMA) methods. The results of the study obtained show that hospitality firms in Indonesia are still filled with uncertainty, as seen by the volatility of stock prices in each company. In addition, forecasting results using ARIMA show that the stock prices of several hospitality firms will be more stable in the future. However, several other firms will still be depressed by the impact of Covid-19.